Synthesis of dibenzo[c,e][1,2]diazocines-a new group of eight-membered cyclic azo compounds - Nokubi, Tomomi; Kindt, Stephanie; Clark, Timothy; Kamimura, Akio; Heinrich, Markus (Tetrahedron Letters, 2015)
Despite of a remarkable ring strain hitherto unknown dibenzo[c,e][1,2]diazocines 3 could be prepared from readily available azo compounds 4 under mild Ullmann-type reaction conditions. The obtained stereoisomers of the new heterocycles 3 were structurally assigned by 2D NMR experiments and DFT calculations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Radical reactions; Azo compounds; Ullmann coupling; Diazocines; Heterocycles